Ranked k-NN Crowdsourced Model for Cloud Internet of Things (CIoT) - Duraipandian, M. (Journal of ISMAC, 2020)
Internet of Things (IoT) has gained more attention in recent years and its influence over future internet is projected to be more as a promising technology. IoT enables sensors to merge with smart devices to monitor, observe and analyse the real time data. These features make the IoT, a suitable technology, for smart applications. On the other hand, cloud offers a better computing paradigm to store and analyse the data. Cloud reduces the complexities in day today life with its novel applications and services, in an efficient manner. However, present IoT and Cloud solutions are focused towards centralized solutions, which limits the user capacity. To enrich the Cloud integrated IoT benefits, a flexible large-scale data collection and analysis is introduced as crowdsourcing, which provides a new dimension in data mining applications. This research work presents a cloud computing crowdsourced data analysis model implemented over IoT, to obtain better computation speed with improved sensitivity, specificity and accuracy.